Electronification of Automobile Marketing: A case study on TATA EV CURVV - Prithu Sarkar; Dr. Romica Bhat (International Journal of Educational Excellence and Innovation, 2025)
In the edge of global warming, depletion of ozone layer, changing dynamics of environment and ecosystem the automobile industry is also getting into the environment friendly mode of automobile production to maintain the sustainability of the ecosystem. The purpose of this chapter is to understand the changing dynamics of automobile marketing to tap the virgin market which leads to the electronic vehicles market. Many companies are many companies targeting this market to change the automobile market ecosystem from swimming from traditional petrol, diesel driven carsto completely automated electronic vehicles. Marketing strategies of the companies are also changing to tap the mindset of the consumers to shift the Perception off selection of a car from the traditional mode off ignition of an engine with the help of the natural fuel to the lithium battery driven cars. Out of the big basket of automobile industry this chapter will examine one of the pioneer EV cars of Tata automobile industry based on its STP study.